Reduced masticatory stimuli modulate myokine secretion in the masseter muscle in mice - Marin Kawasaki; Chiho Kato; Moe Tanigawa; Eri Misawa; Keigo Nakamura; Haruka Inaba; Yasunori Abe; Satoshi Kokai; Takashi Ono (PLoS ONE, 2026)
Mastication is essential for oral function and systemic metabolic regulation. The impact of soft diets, which reduce masticatory load, on myokine signaling remains unclear. Accordingly, we examined whether reduced mastication alters myokine secretion from the masseter muscle and affects muscle development and systemic metabolic regulation. Male C57BL/6J mice were fed either hard or soft diets for short-term (1 week) or long-term (7 weeks). Body weight, masseter muscle weight, epididymal fat weight, and fiber cross-sectional area were assessed. The expression of key myokines (IL-6, IL-10, TNF-α, Nfkb1, and myostatin [Mstn]) was measured using qPCR (quantitative polymerase chain reaction), and myostatin protein levels were evaluated using immunohistochemical assays. Short-term soft diet feeding did not produce any major morphological changes. However, long-term feeding significantly reduced masseter weight and fiber size, while increasing the amount of epididymal fat, despite an unchanged total body weight. At the molecular level, IL-6 expression was consistently lower in soft diet-fed mice, and IL-10 levels declined further with long-term feeding. In contrast, TNF-α, Nfkb1, and Mstn levels were elevated at both ages. The immunohistochemical assays confirmed increased myostatin protein levels in the masseter under soft-diet conditions. These results suggest that reduced masticatory stimulation remodels the biochemical environment of the masseter muscle, suppressing anabolic and anti-inflammatory signals while enhancing catabolic pathways. These alterations impair muscle growth and promote fat accumulation indicating that masticatory load regulates craniofacial muscle development and systemic metabolism through myokine-mediated mechanisms. Therefore, maintaining adequate mastication during growth may be critical for oral health, body composition, and long-term metabolic homeostasis.